Antimicrobial properties of single-donor-derived, platelet–leukocyte fibrin for fistula occlusion: An in vitro study. (December 2013) - Wu, Xiuwen; Ren, Jianan; Yuan, Yujie; Luan, Jianfeng; Yao, Genhong; Li, Jieshou
<x xml:space="preserve">Abstract</x> Fibrin glue is a promising alternative for low-output enterocutaneous fistula closure. Bacterial flora colonizing inside the fistula tract, however, may limit the glue application. Single-donor-derived, platelet-rich materials were hypothesized in this study to have antimicrobial activity against Gram-negative microorganisms. Platelet–leukocyte fibrin (PLF), platelet-rich plasma (PRP), and platelet-poor plasma (PPP) were obtained from healthy volunteers. The amounts of platelet, leukocyte, and complement/antibody were determined. In vitro laboratory susceptibility to PLF and plasmas was determined by the Kirby–Bauer disc-diffusion method. Antimicrobial activity of PLF, PRP, and PPP against three Gram-negative ATCC strains was determined in a bacterial kill assay. Levels of complement and antibody did not significantly differ among PLF, PRP, and PPP (p > 0.05), while platelet and leukocyte counts in platelet-rich biomaterials were significantly higher than those in PPP (p < 0.001). The bactericidal effects produced by PLF and PRP were more pronounced than those by PPP in both qualitative and quantitative aspects. No inhibitory zones against three Gram-negative organisms were observed in the Bioseal®. In conclusion, our homemade PLF, as compared with commercial products, had remarkable antimicrobial activity against Gram-negative bacteria relevant to fistula colonization. The presence of platelets and leukocytes may play an important role in bacterial defense. This is the first study to demonstrate the antibacterial properties of single-unit PLF for fistula closure, presenting a new opportunity for glue sealing.